Study on the Mechanism of Fiber Fracturing Fluid Controlling Pulverized Coal Transportation - Wei Wang; Haifeng Zhao (Energies, 2022)
In view of the problems associated with coal powder production in the development of Coalbed Methane (CBM), a fiber fracturing fluid technology is proposed to control pulverized coal production. Based on a force analysis of coal powder in the fracture and the microstructure of fiber-proppant, a critical intercepted particle size model of coal powder is established. This model is primarily related to fiber properties, proppant particle size and flow rate. To verify this, an FCES-100 device (Nantong Yichuang Experimental Instrument Co., Ltd., Nantong, China) was used to study the influence of fibers on the transportation of pulverized coal in the proppant pack. Five groups of comparative experiments were set up using no fiber, 0.25 g undegraded fiber, 0.25 g degradable fiber, 0.5 g undegraded fiber and 0.5 g degraded fiber, with the flow rate and closure pressures controlled, and, finally, particle size analysis of the discharged pulverized coal was performed using a laser particle size analyzer. The experimental results have shown that the space network structure formed by fiber-proppant can effectively intercept coal powder, reduce the coal powder migration and agglomeration, and eventually improve the fracture conductivity. The results further indicate that, with the increase of the flow rate, the coal particle size shows an increasing trend. The comparison between the particle size of the pulverized coal and the model calculation results demonstrate that the average error is 14.3% and the maximum error is 21.4%. Fiber fracturing fluid technology provides new directions for pulverized coal treatment.